PERBANDINGAN SISTEM ADMINISTRASI PUBLIK ANTARA INDONESIA DAN JEPANG DALAM MENGHADAPI BIROKRASI MODERN - Karisma, Nurul; Aminullah (As-Sulthan Journal of Education, 2026)
The development of modern bureaucracy reflects the need for an adaptive,afficient,and accountable public administration system in responding to global dynamics, tecnological advancement,and increasing public demands for high-quality public service. This article aims to compare the public administration systems of Indonesia and Japan in addressing the challeges of modern bureaucracy. The study employs a deskriptive approach using a comprative method, based on the analysis of policy documents,goverment performance repots,and relevant literature on public administration reform in both countries. The findings indicate that japan possesses a relatively stable public  administration system characterized by a professional bureaucracy,strong inter-agency coordination, and a work culture that emphasizes discipline and policy continuity. Meanwhile,  Indonesia continues to face various challenges in bureaucratic modernization,including regulatory complexity, institutional fragmentation,and iconsistecies in the implementation of bureaucratic reforms, despite notable progress through the adoption of performance manajement and the digitalization of public services. This study concludes that differences in instutional context, bureaucratic culture, and public administration capacity significantly influence the ability of both countries to manage modern bureaucratly. The findings are expected to contribute theoritically to the field of comprative public administration and serve as a practical reference for the formulation of bureacratic reform policies in Indonesia.